2003
DOI: 10.4269/ajtmh.2003.68.115
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Permethrin-Treated Bed Nets on the Spatial Distribution of Malaria Vectors in Western Kenya

Abstract: The effect of insecticide (permethrin)-treated bed nets (ITNs) on the spatial distribution of malaria vectors in neighboring villages lacking ITNs was studied during a randomized controlled trial of ITNs in western Kenya. There was a trend of decreased abundance of Anopheles gambiae with decreasing distance from intervention villages both before (P ‫ס‬ 0.027) and after (P ‫ס‬ 0.002) introduction of ITNs, but this trend was significantly stronger after ITNs were introduced (P ‫ס‬ 0.05). For An. funestus, no pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
121
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(127 citation statements)
references
References 36 publications
5
121
0
Order By: Relevance
“…48 It is likely that the mass killing effect on mosquito populations will have resulted in an underestimate of the impact of ITNs on malaria in pregnancy in the current study. In a separate analysis presented elsewhere, it is shown that the community effect results in a reduction in malaria-related morbidity in young children living in control households within 300 meters of an intervention village.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…48 It is likely that the mass killing effect on mosquito populations will have resulted in an underestimate of the impact of ITNs on malaria in pregnancy in the current study. In a separate analysis presented elsewhere, it is shown that the community effect results in a reduction in malaria-related morbidity in young children living in control households within 300 meters of an intervention village.…”
Section: Discussionmentioning
confidence: 86%
“…16 Furthermore, if mothers continue to use the ITN post-partum, newborns, even from grand multigravidae, that share the sleeping space with their mothers will likely benefit from reduced malaria exposure in the first few months of life. 54 Lastly, targeting of all pregnancies, instead of a selected group of high-risk ones, will increase coverage and contribute to any community effect on malaria transmission, 48 and the likelihood of attaining the target of 60% coverage of high risk groups as stated in the Abuja declaration. 55 The potential to benefit the pregnant woman and the growing fetus during the first four pregnancies, as well as, with continued use, mother and newborn in the post-partum period, and eventually the mother prior to, and during the next pregnancy, is a particularly attractive feature of ITNs.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 In a randomized trial of an ITN distribution program at the village level in Western Kenya, the positive impacts of ITN distribution on child mortality, anemia and malaria infection were as strong among non-beneficiary households within 300 meters of beneficiary villages as they were among households in the beneficiary villages themselves (Gimnig et al, 2003;Hawley et al, 2003). 15 While ITNs may have positive externalities at low levels of coverage (e.g.…”
Section: Background On Insecticide-treated Nets (Itns)mentioning
confidence: 99%
“…Interventions such as use of indoor residual spray (IRS) and long-lasting insecticidal nets take advantage of species-specific vector behaviors that result in exposure to lethal insecticide. [1][2][3][4][5] In many areas, multiple vector species contribute to malaria infection, which may prolong the transmission season through their different feeding behaviors and exploitation of the environment. 3,6 There may also be more vector species in some areas than are presently known due to lack of regular in-depth descriptive surveys, the presence of cryptic or sibling species, [7][8][9] or outdated keys to identify specimens, and inadequate descriptions used to morphologically identify species.…”
Section: Introductionmentioning
confidence: 99%